On the Marxist Theory of Law - Rybakovas, Vladas (Problemos, 1969)
K. Marx's theory of law accentuating the decisive role of economic factors in the process of formation of legal relations and ideas has given rise to its diverse interpretations by bourgeois theoreticians. Normativists (H. Kelzen and others) relate legal views of K. Marx to the natural law trend. Various “sociologist” schools call K. Marx a “vulgar”, “one-sided” materialist. They both do not give sufficient consideration to theoretical propositions of the Marxist theory on the close connection between the economic content and legal form of social relations, as well as peculiarities of ideological process in a class society. The article sheds light upon K. Marx’s use of logical and historical methods of investigation, his discrimination between material relations and their ideological cover. It shows that K. Marx discloses by this the actual role of economic processes in the origin and change of law.